2008
DOI: 10.1007/s10499-008-9207-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ulva meal on growth, feed utilization, and body composition of juvenile Nile tilapia (Oreochromis niloticus) at two levels of dietary lipid

Abstract: A nutrition trial was conducted to investigate the effects of dietary lipid levels and supplemental Ulva meal on growth performance, feed efficiency, nutrient utilization, and body composition of juvenile Nile tilapia, Oreochromis niloticus. Four isonitrogenous (CP 40%) diets containing 0% and 5% Ulva meal were formulated to contain 10% (lowlipid; LL) and 20% (high-lipid; HL) crude lipid. Triplicate groups of fish (*10 g) were fed to apparent satiation three times daily for 16 weeks. Fish fed 5% Ulva meal show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 24 publications
5
74
1
1
Order By: Relevance
“…According to Chapman and Chapman [42], 100 g seaweed provides more than the daily requirement of Vitamin A, B1 and B12 and two thirds of Vitamin C. Also seaweeds are natural sources of hydrosoluble and liposoluble vitamins, such as thiamine and riboflavin, b-carotene and tocopherols, as well as of long-chain polyunsaturated essential fatty acids from the omega-3 (ω-3) (family such as eicosapentaenoic acid [43]. Moreover, Some dietary macroalge meals are improved the growth, lipid metabolism, physiological activity, stress response, disease resistance and carcass quality of various fish species [44][45][46]. So gut weed can be used as a direct feed or as ingredient in diets for herbivorous fish according to Teimouri et al [47].…”
Section: Growth Performancementioning
confidence: 99%
See 1 more Smart Citation
“…According to Chapman and Chapman [42], 100 g seaweed provides more than the daily requirement of Vitamin A, B1 and B12 and two thirds of Vitamin C. Also seaweeds are natural sources of hydrosoluble and liposoluble vitamins, such as thiamine and riboflavin, b-carotene and tocopherols, as well as of long-chain polyunsaturated essential fatty acids from the omega-3 (ω-3) (family such as eicosapentaenoic acid [43]. Moreover, Some dietary macroalge meals are improved the growth, lipid metabolism, physiological activity, stress response, disease resistance and carcass quality of various fish species [44][45][46]. So gut weed can be used as a direct feed or as ingredient in diets for herbivorous fish according to Teimouri et al [47].…”
Section: Growth Performancementioning
confidence: 99%
“…Also, Ergün et al [44] suggested that low-level inclusion of Ulva meal can significantly improve growth performance and nutrient utilization of tilapia fed high-lipid diets.…”
Section: Feed Utilization Efficiencymentioning
confidence: 99%
“…The water temperature at both sites and at the culture depth ranged 22-24°C (July to September) and with the red alga . Ergün et al (2009) reported an increase in the growth of Nile tilapia Oreochromis niloticus when Ulva rigida was added at a level of 50 g kg -1 feed while Stadtlander et al (2013) reported an increase in growth in tilapia when P. yezoensis was added at 136 g kg -1 , but not when added at 272 g kg -1…”
Section: Algae Culturementioning
confidence: 99%
“…Macroalgae have successfully been incorporated into fish and shrimp feeds at levels up to approximately 100 g kg -1 feed without compromising growth or survival , Valente et al 2006, Khan et al 2008, Ergün et al 2009). Occasionally, increases in feed consumption and growth have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Catla catla fed with Cynodon dactylon incorporated diet showed the increased activity of digestive enzymes such as amylase and protease which enhanced digestion and absorption of nutrients essential for fish growth [44]. Inclusion of 5% Ulva in the diet of Nile tilapia improved the growth, feed efficiency, nutrient utilization and body composition [46]. Oreochromis niloticus fingerlings fed with dietary herbal powder (Superliv®) improved weight gain, FCR, protein efficiency ratio (PER) and SGR [47].…”
Section: Introductionmentioning
confidence: 99%